2022
DOI: 10.3390/ijms23031645
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Metabolic Signatures of PPARD-Overexpressing Gastric Tumors

Abstract: Peroxisome proliferator-activated receptor delta (PPARD) is a nuclear receptor known to play an essential role in regulation of cell metabolism, cell proliferation, inflammation, and tumorigenesis in normal and cancer cells. Recently, we found that a newly generated villin-PPARD mouse model, in which PPARD is overexpressed in villin-positive gastric progenitor cells, demonstrated spontaneous development of large, invasive gastric tumors as the mice aged. However, the role of PPARD in regulation of downstream m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Oxypurinol is a metabolite with a high differential ploidy, with a differential expression ploidy (fold change) value as high as 16.45. It has the function of reducing lipid peroxide accumulation and scavenging the production of cellular superoxide radicals; some studies have found that its expression level is significantly increased in gastric tumors [ 51 , 52 ]. The increase in SOD enzyme activity in colon cancer cells after Fn evs treatment may be related to this.…”
Section: Resultsmentioning
confidence: 99%
“…Oxypurinol is a metabolite with a high differential ploidy, with a differential expression ploidy (fold change) value as high as 16.45. It has the function of reducing lipid peroxide accumulation and scavenging the production of cellular superoxide radicals; some studies have found that its expression level is significantly increased in gastric tumors [ 51 , 52 ]. The increase in SOD enzyme activity in colon cancer cells after Fn evs treatment may be related to this.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the gastric cancer tumor proliferation and energy fueling in PPARD-driven gastric cancer is dependent on fatty acids rather than glycolysis [66].…”
Section: Gastric Cancermentioning
confidence: 93%
“…The NMR study found significantly altered concentrations of inosine monophosphate ( p = 0.0054), adenosine monophosphate ( p = 0.009), UDP-glucose ( p = 0.0006), and oxypurinol ( p = 0.039) as PPARD mice aged from 10 weeks to 35 weeks and 55 weeks. LC–MS studies showed decreased concentrations of palmitic acid ( p = 0.0029), oleic acid ( p = 0.0007), steric acid ( p = 0.0028), and linoleic acid ( p = 0.0015) in 55 week old PPARD mice compared to 10 week old PPARD mice [ 66 ]. These results suggested that the gastric cancer tumor proliferation and energy fueling in PPARD-driven gastric cancer is dependent on fatty acids rather than glycolysis [ 66 ].…”
Section: Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse model of PPARβ/δ overexpression in gastric progenitor cells demonstrated the development of invasive gastric tumors in aging animals. Metabolic profiling revealed that these tumors do not require glycolysis but fatty-acid oxidation for tumor progression [ 407 ]. Additionally, a high-fat diet has been shown to induce fatty-acid oxidation depending on PPARβ/δ, which is associated with intestinal stem cell activation and enhanced tumorigenesis [ 408 ], as well as colorectal metastasis formation via the activation of Nanog in colonic cancer stem cells [ 320 ].…”
Section: Ppars and Tumor Metabolismmentioning
confidence: 99%